Study on Microbiological Organisms Responsible For Chronic Osteomyelitis Of the Jaw in Bangladesh - Moral, AKM Sobhan; Begum, Taslima; Rahman, AFM Shahidur; Hasan, MD Mokerrom; Islam, Md. Mahfuzul (Bangladesh Journal of Dental Research & Education, 2013)
Bangladesh Journal of Dental Research & Education, Vol. 01, No. 01, January 2011, Page 5-7 DOI: http://dx.doi.org/10.3329/bjdre.v1i1.15793